1995
DOI: 10.1002/sia.740230708
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of algorithms for background correction in XPS

Abstract: In the present interlaboratory comparison, the consistency and validity of the Shirley, straight-line and Tougaard methods for determination of peak intensities from measured XPS spectra have been studied by analysis of data on Au and Ni taken at eight laboratories. The reproducibility of the individual measuring systems was determined to be 26%. The RMS scatter around their mean values of the ratio of the peak intensity to the Au 4d peak intensity was 6% for the Tougaard method, 9-10% for the Shirley method a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…29 (for case 2). in Figs 4,8, and 12, although some additional factor is needed to account for the extremely low value of R for participant 15 for case 2. All results from participant 23b and two results from participant 15 for case 2 were much higher than expected from the trends in Figs 27 and 31.…”
Section: Shirley Backgroundmentioning
confidence: 95%
See 1 more Smart Citation
“…29 (for case 2). in Figs 4,8, and 12, although some additional factor is needed to account for the extremely low value of R for participant 15 for case 2. All results from participant 23b and two results from participant 15 for case 2 were much higher than expected from the trends in Figs 27 and 31.…”
Section: Shirley Backgroundmentioning
confidence: 95%
“…They found that peak intensities obtained using the Tougaard method for background subtraction agreed much better with the calculated intensities than those obtained with the linear and Shirley methods. An additional assessment of the three methods was reported by Jansson et al [8] who analyzed peak intensities obtained using the three methods from XPS spectra of Ni and Au measured in eight laboratories. Ratios of intensities of Ni and Au peaks to the Au 4d intensity were compared with ratios of the corresponding calculated intensities.…”
mentioning
confidence: 98%
“…13. In addition to the individual factors in the design leading to signiÐcant di †erences in peak BE biases, the interactions among factors were also signiÐcant at the 5% signiÐcance level in many of the data sets.…”
Section: Analysis Of Variance : Bias In the Binding Energy Of The Larmentioning
confidence: 96%
“…The users' community tries to help the overall understanding of the evaluation needs through issuing standard spectral data [3,4] and making inter-laboratory comparisons [5] of the sample handling and data evaluation methods. Some data evaluation methods have been inherited from the nuclear spectroscopy [6], some others have been derived after facing field-specific problems [7,2].…”
Section: Implementation and Documentation Problemsmentioning
confidence: 99%